Diksi Bung Karno dalam Memoar Sarinah: Sebuah Analisis Wacana Kritis Feminis Model Sara Mills - Suyanto, Suyanto (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
This study aims to explain the use of words or phrase categories: general form; mark and not mark; naming and androcentrism; and semantic derogation in Sarinah's memoir. The material object of this research is Sarinah's memoir, written by Bung Karno and formal object is words and phrases used in Sarinah's memoir. Obtaining the data of this study uses the refer method. Data analysis was used the matching (padan) method. This study uses a tool analysis of the theory of critical analysis of feminist stylistics in Sara Mills's model. The results of the data analysis show that naming and androcentrism, such as the soft or weak, the stupid, the short-minded, the nerimo, the beauty, and the